STRATEGI PENGELOLAAN PURA AGUNG BESAKIH SEBAGAI DESTINASI WISATA BUDAYA: PENDEKATAN GAME THEORY - WIBAWA, GEDE ADITYA SURYA; TASTRAWATI, NI KETUT TARI; KENCANA, EKA N. (E-Jurnal Matematika, 2023)
In the context of managing Pura Agung Besakih as a cultural tourism destination, consideration is needed from the operational management of the Besakih Temple area and the travel agency so that in addition to getting the maximum expected benefits, the preservation of the place and culture, as well as the smooth running of religious ceremonies at Pura Agung Besakih, can also be maintained. In decision-making by the operational management of the Besakih Temple area and the travel agency, this study used a game theory approach by applying a non-zero-sum game. This study uses simulation data related to the number of visits by foreign and domestic tourists and the expectations of opinions from the operational management of the Besakih Temple area and the travel agency. The results obtained are that the best strategy used by the operational management of the Besakih Temple area is full access and by the travel agency is to use tourist delivery services without tour packages.